Nutraceutical Study on Maianthemum atropurpureum, a Wild Medicinal Food Plant in Northwest Yunnan, China - Xu, Li; Wang, Yizhou; Ji, Yuanyuan; Li, Ping; Cao, Wujisiguleng; Wu, Shibiao; Kennelly, Edward; Long, Chunlin (Frontiers in Pharmacology, 2021)
Maianthemum atropurpureum (Asparagaceae), called nibai in Tibetan or dongka in Drung or zhu-ye-cai in local Chinese, is a wild vegetable consumed by the Tibetan people and other ethnic groups in Northwest Yunnan, China. It is also a traditional medicinal plant used by different linguistic groups for anti-microbial and anti-tumor purposes. However the nutritional and phytochemical compositions of this important medicinal food plant have not been well studied previously. In this study, the nutrient content for nibai was determined by the China National Standards (GB) methods, and the phytochemical analysis involved multiple chromatographic and spectral methods including LC-TOF-MS analysis (Figure 1). Dried nibai is a rich source of protein (ca. 24.6%), with 18 of the 20 common amino acids. The amino acid content of nibai can reach up to 17.9 g/100 g, with the essential amino acids as major contributors, corresponding to 42.3 % of the total amino acids. Nibai contains rich mineral elements, dietary fiber, vitamins, β-carotene, carbohydrates, and lipids. The phytochemical content of nibai was examined by conventional isolation strategies, as well as HR-ESI-TOF-MS to detect and identify 16 compounds including nine steroid saponins and seven flavonoids. Among these compounds, 2, 3, 4, and 6 were found from the genus Maianthemum for the first time. These results help to confirm that the local people’s practice of consuming Maianthemum atropurpureum is warranted due to its high levels of vitamins, minerals, essential amino-acids, and phytochemicals. Nibai may be further developed in Tibet and surrounding regions, and beyond as a health food, nutraceutical, and/or dietary supplement product.